Thermal performance of three horizontal ground heat exchanger systems: comparison of linear-loop, spiral-coil and slinky-coil arrangements - Hu, Linwei; Rizvi, Zarghaam Haider; Tobber, Lisa; Wuttke, Frank (Frontiers in Energy Research, 2023)
Ground source heat pumps (GSHPs) are highly efficient for heating and cooling buildings. Among the different types of ground source heat pumps, horizontal ground heat exchangers (HGHEs) gaining popularity due to their cost-effectiveness, ease of installation and high regeneration capacity. However, studies on the interaction and influence of the local environment with the HGHE and the thermal performance influenced by the arrangement and performance of the HGHE are insufficient. This study uses a three-dimensional numerical model to simulate three types of HGHEs, including linear-loop, spiral-coil, and slinky-coil arrangements. Instead of just one unit, three units are connected in series or parallel. The model considers the energy balance and the heat transfer and exchange processes between the heat exchanger and the soil. Simulation of cooling and heating for 1 year revealed that the slinky-coil arrangement is the most affected by heat fluxes at the ground surface, because of its maximum length, which leads to its lowest coefficient of performance (COP) value. The thermal performance of linear-loop and spiral-coil arrangements is similar, but considering the material cost, the linear-coil arrangement has the lowest installation cost and operating cost for 30 years.